A Bibliographic Handbook Management Information Systems - Joplin, Alan L., Comp. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1980)
Over 400 publications related to all aspects of the Management Information Systems concept are listed in this bibliography. The materials deal not only with the Management Information Systems concept specifically, but with the organizational and theoretical context in which the systems approach to management operates. In other words, the topics covered include aspects of planning, decision making, management theory, organizational environment, organizational evaluation, systems analysis, and other conceptual areas as they relate to management systems generally and Management Information Systems in particular. No annotations are provided and the listing is strictly alphabetical by author. (PGD)
Availability: Alan L. Joplin, 3106 Evans, Saint Louis, MO 63106 ($4.00 plus $1.00 postage).
Microfiche.
Keywords: Administration; Decision Making; Elementary Secondary Education; Evaluation; Management Information Systems; Management Systems; Organization; Organizational Climate; Planning; Postsecondary Education; Systems Approach; Reference Materials, Bibliographies